2010
DOI: 10.1523/jneurosci.2064-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Brain Dynamics Underlying Training-Induced Improvement in Suppressing Inappropriate Action

Abstract: Inhibitory control, a core component of executive functions, refers to our ability to suppress intended or ongoing cognitive or motor processes. Mostly based on Go/NoGo paradigms, a considerable amount of literature reports that inhibitory control of responses to "NoGo" stimuli is mediated by top-down mechanisms manifesting ϳ200 ms after stimulus onset within frontoparietal networks. However, whether inhibitory functions in humans can be trained and the supporting neurophysiological mechanisms remain unresolve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
83
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(99 citation statements)
references
References 64 publications
15
83
1
Order By: Relevance
“…This pattern contrasts with previous evidence for the development of automatic, feed-forward forms of inhibition induced by training with a Go/NoGo task (Manuel et al, 2010). This difference in the effect of practice with an SST versus a Go/NoGo task likely follow from the fact that in SST task, Go stimuli are inconsistently associated with Go and NoGo goals, whereas in Go/NoGo task, repeated associations between NoGo stimuli and NoGo goals enable the development of stimulus-driven inhibition (Shiffrin and Schneider, 1977;Verbruggen and Logan, 2008a).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This pattern contrasts with previous evidence for the development of automatic, feed-forward forms of inhibition induced by training with a Go/NoGo task (Manuel et al, 2010). This difference in the effect of practice with an SST versus a Go/NoGo task likely follow from the fact that in SST task, Go stimuli are inconsistently associated with Go and NoGo goals, whereas in Go/NoGo task, repeated associations between NoGo stimuli and NoGo goals enable the development of stimulus-driven inhibition (Shiffrin and Schneider, 1977;Verbruggen and Logan, 2008a).…”
Section: Discussioncontrasting
confidence: 99%
“…While inhibitory control has been extensively studied (Chambers et al, 2009;Aron, 2011), the behavioral and brain plastic changes induced by practicing inhibition tasks remain largely unresolved. Manuel et al (2010) demonstrated that training on a Go/ NoGo task improved inhibitory control performance, but that the behavioral improvement was not supported by a modification of the global frontoebasal inhibitory control network. Rather, neuroplastic changes manifested within temporoparietal cortices over the initial stages of the processing of the stimuli, indicative of the development of stimulus-driven, feed-forward forms of inhibition directly triggered by the NoGo stimuli (Manuel et al, 2010;Shiffrin and Schneider, 1977).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Inhibitory control (IC), the ability to suppress ongoing or planned cognitive or motor processes, can be improved with short-(50 min in Verbruggen and Logan 2008;Manuel et al 2010;Manuel et al 2013) to medium-term training (ca. 10-15 h in Thorell et al 2009;Johnstone et al 2012;Berkman et al 2014;Chavan et al 2015).…”
Section: Introductionmentioning
confidence: 99%